Quantum chemical calculation of the (S)-9-(2,3-dihydroxypropyl)adenine molecule. - Havlas, Z (1980)
Quantum chemical calculations of conformational maps of the molecule of a new virostatic agent (S)-9-(2,3-dihydroxypropyl)adenine were performed. The thermodynamically most advantageous conformation I corresponds, for the D-series, to the alpha-ribo configuration, while the following minima, which are close in energy (II,III), correspond to beta-ribo and beta-xylo configurations.